Interface self-repairing anchor rod material and preparation method thereof

By introducing multiple hydrogen bond self-healing molecules into the anchor material, the self-healing of the material is achieved by using hydrogen bonding, the problem of cracking and damage of anchor material caused by large deformation of the surrounding rock in the tunnel is solved, and the durability and mechanical properties of anchor support are improved.

CN119751733AInactive Publication Date: 2025-04-04CCTEG COAL MINING RES INST +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411865557.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When the surrounding rock in the tunnel continues to undergo large deformation, the anchor material is prone to produce a large number of cracks due to cracking and damage, which seriously affects the effect of anchor support.

Method used

An interface self-healing anchor material is used, which consists of anchor matrix monomer material, polymerization initiator, crosslinking agent, crosslinking promoter, enhancer, plasticizer, self-healing molecule and solubilizer. The self-healing of the material is achieved through the hydrogen bond between the multiple hydrogen bond self-healing molecule and the anchor matrix.

Benefits of technology

This material can repair itself when cracked and damaged by tunnel deformation, effectively guaranteeing the long-term durability of anchor support and reinforcement, and improving the mechanical properties and impact resistance of anchor rods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751733A_ABST
    Figure CN119751733A_ABST
Patent Text Reader

Abstract

The invention provides an interface self-repairing anchor rod material and a preparation method thereof. The interface self-repairing anchor rod material comprises the following components in parts by mass: 90-100 parts of an anchor rod matrix monomer material, 1-2 parts of an anchor rod matrix polymerization initiator, 5-8 parts of an anchor rod matrix cross-linking agent, 1-2 parts of an anchor rod matrix cross-linking accelerant, 1-3 parts of a reinforcing agent, 1-2 parts of a plasticizer, 25-30 parts of self-repairing molecules and 1-3 parts of a solubilizer. The anchor rod material provided by the invention can be self-repaired when the anchor rod material is cracked and damaged due to roadway deformation to generate a large number of cracks, so that the long-term durability of anchor rod supporting and reinforcing is effectively guaranteed, and the reinforcing effect is outstanding. The invention further provides a preparation method of the anchor rod material. The preparation method has the advantages of being simple in process, low in cost and easy to apply and popularize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of anchor rod new material support, and in particular to an interface self-repairing anchor rod material and a preparation method thereof. Background Art

[0002] As the depth of coal mining increases, the problem of continuous rheological large deformation of tunnel surrounding rock seriously affects the mining of the working face. Anchor support is an effective means of controlling tunnel surrounding rock, and anchor material is the core of grouting modification. Metal anchor material has unique advantages with its low price, mechanical strength and environmental protection performance, and has achieved good results in tunnel support and reinforcement applications. However, in the continuous rheological large deformation tunnel support reinforcement, the anchor material is cracked and damaged by the deformation of the tunnel, resulting in a large number of cracks, which seriously affects the effect of anchor support and is the most important restrictive factor for tunnel surrounding rock anchor support. Therefore, it is urgent to develop new interface self-repairing anchor materials and preparation methods. Summary of the invention

[0003] The present application aims to solve at least one of the technical problems in the related art to a certain extent. The present application proposes an interface self-repairing anchor material and a preparation method thereof. The anchor material provided by the present application can self-repair when the anchor material is cracked and damaged by the deformation of the roadway and produces a large number of cracks, effectively ensuring the long-term durability of the anchor support reinforcement.

[0004] According to an embodiment of the first aspect of the present application, an interface self-repairing anchor material is proposed, comprising the following components in parts by mass: 90-100 parts of anchor matrix monomer material, 1-2 parts of anchor matrix polymerization initiator, 5-8 parts of anchor matrix cross-linking agent, 1-2 parts of anchor matrix cross-linking promoter, 1-3 parts of reinforcer, 1-2 parts of plasticizer, 25-30 parts of self-repairing molecules and 1-3 parts of solubilizer.

[0005] In some embodiments, the anchor matrix monomer material includes butadiene, 1,1-dichloroethylene and allyl fluoride in a mass ratio of 1:2:5.

[0006] In some embodiments, the anchor matrix polymerization initiator is 1,1-diphenylhexyllithium.

[0007] In some embodiments, the anchor matrix crosslinking agent includes N,N-dimethylisoquinoline-4-sulfonamide and propylamine sulfonamide in a mass ratio of 2:1.

[0008] In some embodiments, the anchor matrix cross-linking promoter includes 2-methacryloyloxyethyl lipoate and potassium glycol sulfate in a mass ratio of 3:1.

[0009] In some embodiments, the reinforcing agent includes nano-iridium powder and nano-tungsten powder in a mass ratio of 1:1; the plasticizer includes heptylnonylphthalate and diundecylphthalate in a mass ratio of 1:1.

[0010] In some embodiments, the self-healing molecules include 2,2-bis[4-(2,3-dibromopropoxy)-3,5-dibromophenyl], octabromodiphenyl ether and 2,4,6-tribromopyrimidine, 2-amino-4,6-dibromopyrimidine in a mass ratio of 1:2:1:1.

[0011] In some embodiments, the solubilizer includes dimethylsiloxane-(85-90% ethylene oxide) block copolymer and poly(ethylene oxide)-block-polycaprolactone in a mass ratio of 2:1.

[0012] According to an embodiment of the second aspect of the present application, a method for preparing an interface self-repairing anchor material is provided, comprising the following steps: mixing an anchor matrix monomer material, a reinforcing agent, a self-repairing molecule, a solubilizing agent, and a plasticizer according to stoichiometry to obtain a mixed matrix material;

[0013] Adding an anchor matrix polymerization initiator, an anchor matrix crosslinking agent, and an anchor matrix crosslinking accelerator to the mixed matrix material according to chemical measurements, mixing well, and then heating and melting to form a mixed solution A;

[0014] The mixed solution A is introduced into a specific mold and heated to 160-180° C., and reacted for 60-70 minutes; the reactants are cooled and solidified to obtain the anchor material described in any of the above embodiments.

[0015] In some embodiments, the mixed matrix material melts at a heating temperature of 130-150°C.

[0016] This application uses olefins with multiple carbon-carbon double bonds as anchor rod matrix materials, adds self-repairing molecular materials with multiple hydrogen bond functional groups, and then undergoes polymerization and cross-linking reactions under the action of anchor rod matrix initiators, cross-linking agents and cross-linking promoters to prepare interface self-repairing anchor rod materials that can self-repair cracks. Ultimately, the development of an interface self-repairing anchor rod material and its preparation method with simple method, low cost and outstanding reinforcement effect is achieved.

[0017] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:

[0019] Figure 1It is a flow chart of the method for preparing anchor rod materials proposed in one embodiment of the present application. DETAILED DESCRIPTION

[0020] Embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be construed as limiting the present application. On the contrary, the present application includes all changes, modifications and equivalents that fall within the spirit and connotation of the appended claims.

[0021] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0022] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0023] To achieve the above-mentioned purpose, according to an embodiment of the first aspect of the present application, an interface self-repairing anchor material is proposed, comprising the following components in parts by weight: 90-100 parts of anchor matrix monomer material, 1-2 parts of anchor matrix polymerization initiator, 5-8 parts of anchor matrix cross-linking agent, 1-2 parts of anchor matrix cross-linking promoter, 1-3 parts of enhancer, 1-2 parts of plasticizer, 25-30 parts of self-repairing molecules and 1-3 parts of solubilizer.

[0024] The interface self-repairing anchor material in this embodiment includes 90-100 parts by weight of anchor matrix monomer material, wherein the anchor matrix monomer material includes butadiene (CAS: 106-99-0), 1,1-dichloroethylene (CAS: 75-35-4) and fluorinated allyl (CAS: 818-92-8) in a mass ratio of 1: 2: 5. In some embodiments, the anchor matrix monomer material may be 90 parts, 91 parts, 92 parts, 93 parts, 94 parts, 95 parts, 96 parts, 97 parts, 98 parts, 99 parts or 100 parts by mass. If the anchor matrix monomer material has a small amount, such as less than 90 parts, the molecular weight of the anchor matrix monomer material is low, resulting in low mechanical properties of the interface self-repairing anchor material. If the anchor matrix monomer material has a large amount, such as more than 100 parts, there will be a large amount of unreacted residual monomers, which will affect the mechanical strength of the interface self-repairing anchor material.

[0025] In some embodiments, the interface self-repairing anchor material includes 1-2 parts by weight of an anchor matrix polymerization initiator, wherein the anchor matrix polymerization initiator is 1,1-diphenylhexyl lithium. In some embodiments, the mass fraction of the anchor matrix polymerization initiator may be 1 part or 2 parts, etc. If the mass fraction of the anchor matrix polymerization initiator is small, such as less than 1 part, a large amount of anchor matrix monomer material is not reacted, and there is a large amount of unreacted residual anchor matrix monomer material, which affects the mechanical strength of the interface self-repairing anchor material. If the mass fraction of the anchor matrix polymerization initiator is large, such as greater than 2 parts, the molecular weight of the anchor matrix monomer material is not high, and the mechanical strength of the interface self-repairing anchor material is low.

[0026] In some embodiments, the interface self-repairing anchor material includes 5-8 parts by weight of an anchor matrix crosslinking agent, wherein the anchor matrix crosslinking agent includes N,N-dimethylisoquinoline-4-sulfonamide (CAS: 1306606-93-8) and propylamine sulfonamide (CAS: 147962-41-2) in a mass ratio of 2:1. In some embodiments, the mass fraction of the anchor matrix crosslinking agent is 5 parts, 6 parts, 7 parts or 8 parts, etc. If the mass fraction of the anchor matrix crosslinking agent is small, such as less than 5 parts, the interface self-repairing anchor material has a low crosslinking density and a low elongation at break. If the mass fraction of the anchor matrix crosslinking agent is large, such as greater than 8 parts, uneven crosslinking, high local crosslinking, and uneven performance of the interface self-repairing anchor material are caused.

[0027] In some embodiments, the interface self-repairing anchor material includes 1-2 parts by weight of an anchor matrix cross-linking promoter, and the anchor matrix cross-linking promoter includes 2-methacryloyloxyethyl thioate (CAS: 126449-41-0) and potassium glycol sulfate (CAS: 59599-54-1) in a mass ratio of 3:1. In some embodiments, the mass fraction of the anchor matrix cross-linking promoter may be 1 part or 2 parts, etc. If the mass fraction of the anchor matrix cross-linking promoter is small, such as less than 1 part, the cross-linking rate of the interface self-repairing anchor material is slow and the cross-linking is insufficient. If the mass fraction of the anchor matrix cross-linking promoter is large, such as greater than 2 parts, the cross-linking rate of the interface self-repairing anchor material is fast, the cross-linking is high in some areas, the performance of the interface self-repairing anchor material is uneven, there is stress concentration, and it is easy to break.

[0028] In some embodiments, the interface self-repairing anchor material includes 1-3 parts by mass of a reinforcing agent, and the reinforcing agent includes nano-iridium powder (CAS: 7439-88-5) and nano-tungsten powder (CAS: 7440-33-7) in a mass ratio of 1:1. In some embodiments, the mass fraction of the reinforcing agent can be 1 part, 2 parts, or 3 parts, etc. If the mass fraction of the reinforcing agent is small, such as less than 1 part, the reinforcing effect of the interface self-repairing anchor material is not good and the strength is not high. If the mass fraction of the reinforcing agent is large, such as more than 3 parts, the interface self-repairing anchor material has high rigidity and insufficient flexibility.

[0029] In some embodiments, the interface self-repairing anchor material includes 1-2 parts by weight of a plasticizer, and the plasticizer includes heptyl nonyl phthalate (CAS: 19295-81-9) and diundecyl phthalate (CAS: 96507-86-7) in a mass ratio of 1:1. In some embodiments, the mass fraction of the plasticizer is 1 part or 2 parts, etc. If the mass fraction of the plasticizer is small, such as less than 1 part, the plasticizing effect is not good, the fluidity of each component of the interface self-repairing anchor material is reduced, and the mixing effect is not good. If the mass fraction of the plasticizer is large, such as more than 2 parts, there are many residual small molecules, forming defects and holes, which affect the mechanical strength of the interface self-repairing anchor material.

[0030] In some embodiments, the interface self-repairing anchor material includes 25-30 parts by weight of self-repairing molecules, and the self-repairing molecules include 2,2-bis[4-(2,3-dibromopropoxy)-3,5-dibromophenyl]propane (CAS: 21850-44-2), octabromodiphenyl ether (CAS: 32536-52-0), 2,4,6-tribromopyrimidine (CAS: 36847-11-7), and 2-amino-4,6-dibromopyrimidine (CAS: 856973-26-7) in a mass ratio of 1:2:1:1. In some embodiments, the mass fraction of the self-repairing molecules is 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, or 30 parts. If the mass fraction of the self-repairing molecules is small, such as less than 25 parts, the self-repairing rate of the interface self-repairing anchor material is low and the repair effect is not good. If the mass fraction of the self-repairing molecules is large, such as greater than 30 parts, the mechanical strength of the interface self-repairing anchor material is affected.

[0031] The self-repairing molecules in this application are combined with 2,2-bis[4-(2,3-dibromopropoxy)-3,5-dibromophenyl]propane, octabromodiphenyl ether, 2,4,6-tribromopyrimidine, 2-amino-4,6-dibromopyrimidine, etc. to generate hydrogen bonding between the anchor rod and the anchor body, thereby enhancing the force between the anchor rod and the anchor body, increasing the anchoring force, and improving the anchoring effect of the anchor rod. When the anchor rod is impacted, the increase in its cohesive energy improves its impact resistance.

[0032] In some embodiments, the interface self-repairing anchor material includes 1-3 parts by weight of a solubilizer, wherein the solubilizer includes a dimethylsiloxane-(85-90% ethylene oxide) block copolymer (CAS: 68938-54-5) and a poly(ethylene oxide)-block-polycaprolactone (CAS: 30174-06-2) in a mass ratio of 2:1. In some embodiments, the mass fraction of the solubilizer may be 1 part, 2 parts, or 3 parts, etc. If the mass fraction of the solubilizer is small, such as less than 1 part, the components in the interface self-repairing anchor material are unevenly dispersed, and the performance of the anchor material is degraded. If the mass fraction of the solubilizer is large, such as greater than 3 parts, the mechanical properties of the interface self-repairing anchor material are affected.

[0033] This application uses multiple hydrogen-bonded self-repairing molecular materials such as 2,2-bis[4-(2,3-dibromopropoxy)-3,5-dibromophenyl]propane, octabromodiphenyl ether, 2,4,6-tribromopyrimidine, and 2-amino-4,6-dibromopyrimidine to prepare an interface self-repairing anchor material. The multiple pyrimidine and halogen molecules produce hydrogen bonds with the matrix, which enhances the internal force of the anchor matrix, increases the cohesive force, improves the mechanical properties of the anchor, and enables the anchor to have interface self-repairing properties. In field applications, when the surrounding rock of the tunnel is greatly deformed and causes cracks in the anchor, the multiple hydrogen bonds of the interface self-repairing molecules produce a self-repairing effect, so that the cracks in the anchor can be automatically repaired.

[0034] According to the embodiment of the second aspect of the present application, a method for preparing an interface self-repairing anchor material is proposed. Figure 1 , including the following steps:

[0035] S1: mixing the anchor matrix monomer material, the reinforcing agent, the self-repairing molecule, the solubilizer and the plasticizer according to the stoichiometric ratio to obtain a mixed matrix material;

[0036] S2: adding the anchor matrix polymerization initiator, the anchor matrix crosslinking agent and the anchor matrix crosslinking accelerator to the mixed matrix material according to the chemical measurement, mixing and heating to melt into a mixed solution A; wherein the mixed matrix material is melted at a heating temperature of 130-150°C;

[0037] S3: introducing the mixed solution A into a specific mold and heating it to 160-180° C., reacting for 60-70 minutes; cooling and solidifying the reactants to obtain the anchor material in any of the above embodiments.

[0038] Specifically, 90-100 parts of anchor matrix monomer material, 1-3 parts of reinforcing agent, 25-30 parts of self-repairing molecules, 1-3 parts of solubilizer and 1-2 parts of plasticizer are weighed in parts by mass, and evenly mixed in a dry powder mixer for 30 minutes to obtain a mixed matrix material; then 1-2 parts of anchor matrix polymerization initiator (1,1-diphenylhexyl lithium), 5-8 parts of anchor matrix cross-linking agent and 1-2 parts of anchor matrix cross-linking promoter are weighed in parts by mass, added to the mixed matrix material, stirred in a dry powder mixer for 20 minutes, heated to 130-150°C, introduced into a mold of a specific shape, heated to 160-180°C, reacted for 60 minutes, cooled and solidified, to prepare the interface self-repairing anchor material described above.

[0039] To facilitate further understanding of the present application, the scheme of the present application is further described below in conjunction with the embodiments. Those skilled in the art will understand that the description in the present application is only part of the examples, and any other suitable specific examples are within the scope of the present application.

[0040] Example 1

[0041] The present embodiment provides an interface self-repairing anchor material, and its preparation method and specific operating parameters are as follows: weigh 90 parts of anchor matrix monomer material, 1 part of reinforcing agent, 30 parts of self-repairing molecules, 2 parts of solubilizers and 2 parts of plasticizers according to mass proportions, stir in a dry powder mixer for 30 minutes to evenly mix, and obtain a mixed matrix material.

[0042] Then, 2 parts of anchor matrix polymerization initiator (1,1-diphenylhexyllithium), 8 parts of anchor matrix cross-linking agent and 1 part of anchor matrix cross-linking accelerator are weighed according to their mass parts and added to the mixed matrix material. The mixture is stirred in a dry powder mixer for 20 minutes and heated to 130-150°C to obtain a mixed solution A. The mixed solution A is introduced into a mold of a specific shape, heated to 160-180°C, reacted for 60 minutes, and cooled and solidified to prepare an interface self-repairing anchor material.

[0043] Example 2

[0044] Compared with Example 1, this embodiment has the following differences: 98 parts of anchor matrix monomer material, 2 parts of reinforcing agent, 27 parts of self-repairing molecule, 1 part of solubilizer and 2 parts of plasticizer are weighed by weight, and stirred in a dry powder mixer for 30 minutes to uniformly mix to obtain a mixed matrix material. Then, 1 part of anchor matrix polymerization initiator (1,1-diphenylhexyl lithium), 7 parts of anchor matrix crosslinking agent and 2 parts of anchor matrix crosslinking accelerator are weighed by weight and added to the obtained mixed matrix material.

[0045] Example 3

[0046] Compared with Example 1, this embodiment has the following differences: 94 parts of anchor matrix monomer material, 3 parts of reinforcing agent, 26 parts of self-repairing molecule, 3 parts of solubilizer and 1 part of plasticizer are weighed by weight, and stirred in a dry powder mixer for 30 minutes to uniformly mix to obtain a mixed matrix material. Then, 2 parts of anchor matrix polymerization initiator (1,1-diphenylhexyl lithium), 5 parts of anchor matrix crosslinking agent and 2 parts of anchor matrix crosslinking accelerator are weighed by weight and added to the obtained mixed matrix material.

[0047] Example 4

[0048] Compared with Example 1, this embodiment has the following differences: 100 parts of anchor matrix monomer material, 1 part of reinforcing agent, 25 parts of self-repairing molecules, 1 part of solubilizer and 1 part of plasticizer are weighed by mass, and stirred in a dry powder mixer for 30 minutes to uniformly mix to obtain a mixed matrix material. Then, 1 part of anchor matrix polymerization initiator (1,1-diphenylhexyl lithium), 6 parts of anchor matrix crosslinking agent and 1 part of anchor matrix crosslinking accelerator are weighed by mass and added to the obtained mixed matrix material.

[0049] Example 5

[0050] Compared with Example 1, this embodiment has the following differences: 93 parts of anchor matrix monomer material, 3 parts of reinforcing agent, 29 parts of self-repairing molecule, 3 parts of solubilizer and 2 parts of plasticizer are weighed by weight, and stirred in a dry powder mixer for 30 minutes to uniformly mix to obtain a mixed matrix material. Then, 2 parts of anchor matrix polymerization initiator (1,1-diphenylhexyl lithium), 8 parts of anchor matrix crosslinking agent and 2 parts of anchor matrix crosslinking accelerator are weighed by weight and added to the obtained mixed matrix material.

[0051] Experimental example

[0052] The anchor rod materials in each embodiment were tested after use, and the results are shown in Table 1.

[0053] Table 1 Performance results of anchor materials in the embodiment

[0054]

[0055] It can be seen from the results in Table 1 that the anchor material provided by the present application can self-repair when the anchor material is cracked and damaged by tunnel deformation and produces a large number of cracks, thereby effectively ensuring the long-term durability of the anchor support reinforcement.

[0056] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0057] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. An interface self-repairing anchor material, characterized in that: The invention comprises the following components in parts by weight: 90-100 parts of anchor matrix monomer material, 1-2 parts of anchor matrix polymerization initiator, 5-8 parts of anchor matrix crosslinking agent, 1-2 parts of anchor matrix crosslinking accelerator, 1-3 parts of reinforcing agent, 1-2 parts of plasticizer, 25-30 parts of self-repairing molecules and 1-3 parts of solubilizing agent.

2. The anchor material according to claim 1, characterized in that: The anchor rod matrix monomer material comprises butadiene, 1,1-dichloroethylene and fluorinated allyl in a mass ratio of 1:2:

5.

3. The anchor material according to claim 1, characterized in that: The anchor matrix polymerization initiator is 1,1-diphenylhexyl lithium.

4. The anchor material according to claim 1, characterized in that: The anchor matrix cross-linking agent comprises N,N-dimethylisoquinoline-4-sulfonamide and propylamine sulfonamide in a mass ratio of 2:

1.

5. The anchor material according to claim 1, characterized in that: The anchor matrix cross-linking accelerator comprises 2-methacryloyloxyethyl lipoate and potassium glycol sulfate in a mass ratio of 3:

1.

6. The anchor material according to claim 1, characterized in that: The reinforcing agent comprises nano iridium powder and nano tungsten powder in a mass ratio of 1:1; the plasticizer comprises heptyl nonyl phthalate and diundecyl phthalate in a mass ratio of 1:

1.

7. The anchor material according to any one of claims 1 to 6, characterized in that: The self-repairing molecules include 2,2-bis[4-(2,3-dibromopropoxy)-3,5-dibromophenyl], octabromodiphenyl ether, 2,4,6-tribromopyrimidine and 2-amino-4,6-dibromopyrimidine in a mass ratio of 1:2:1:

1.

8. The anchor material according to claim 7, characterized in that: The solubilizer comprises dimethylsiloxane-(85-90% ethylene oxide) block copolymer and poly(ethylene oxide)-block-polycaprolactone in a mass ratio of 2:

1.

9. A method for preparing an interface self-repairing anchor material, characterized in that: The following steps are involved: Mixing the anchor matrix monomer material, the reinforcing agent, the self-repairing molecule, the solubilizing agent, and the plasticizer according to the stoichiometric amount to obtain a mixed matrix material; Adding an anchor matrix polymerization initiator, an anchor matrix crosslinking agent, and an anchor matrix crosslinking accelerator to the mixed matrix material according to chemical measurements, mixing well, and then heating and melting to form a mixed solution A; The mixed solution A is introduced into a specific mold and heated to 160-180° C., and reacted for 60-70 minutes; the reactants are cooled and solidified to obtain the anchor material according to any one of claims 1-8.

10. The preparation method according to any one of claim 9, characterized in that: The mixed matrix material is melted at a heating temperature of 130-150°C.